Ethylene promotes seed iron storage during Arabidopsis seed maturation via ERF95 transcription factor. Issue 8 (28th July 2020) - Sun, Ying; Li, Jia Qi; Yan, Jing Ying; Yuan, Jun Jie; Li, Gui Xin; Wu, Yun Rong; Xu, Ji Ming; Huang, Rong Feng; Harberd, Nicholas P.; Ding, Zhong Jie; Zheng, Shao Jian
Abstract: Because Iron (Fe) is an essential element, Fe storage in plant seeds is necessary for seedling establishment following germination. However, the mechanisms controlling seed Fe storage during seed development remain largely unknown. Here we reveal that an ERF95 transcription factor regulates Arabidopsis seed Fe accumulation. We show that expression of ERF95 increases during seed maturation, and that lack of ERF95 reduces seed Fe accumulation, consequently increasing sensitivity to Fe deficiency during seedling establishment. Conversely, overexpression of ERF95 has the opposite effects. We show that lack of ERF95 decreases abundance of FER1 messenger RNA in developing seed, which encodes Fe‐sequestering ferritin. Accordingly, a fer1‐1 loss‐of‐function mutation confers reduced seed Fe accumulation, and suppresses ERF95‐promoted seed Fe accumulation. In addition, ERF95 binds to specific FER1 promoter GCC‐boxes and transactivates FER1 expression. We show that ERF95 expression in maturing seed is dependent on EIN3, the master transcriptional regulator of ethylene signaling. While lack of EIN3 reduces seed Fe content, overexpression of ERF95 rescues Fe accumulation in the seed of ein3 loss‐of‐function mutant. Finally, we show that ethylene production increases during seed maturation. We conclude that ethylene promotes seed Fe accumulation during seed maturation via an EIN3‐ERF95‐FER1‐dependent signaling pathway. Abstract : Plant seeds are the major source of dietary iron for most of world's population, whereas how seed iron storage is regulated remains elusive. This study reveals that the gaseous hormone ethylene accumulates during Arabidopsis seed maturation, and that it promotes seed iron storage via the EIN3‐ERF95‐FER1 signaling module.